Video with Adobe Flash CS4 Professional studio techniques - Reinhardt, Robert 1973- (Peachpit, 2009)
The definitive guide to creating video for the Web In Video with Adobe Flash CS4 Professional Studio Techniques, Robert Reinhardt goes beyond the entry-level coverage found in other books to bring you a comprehensive look at what you really need to know to produce, host, and distribute Flash-compatible video on the Web, including FLV and AVC/H.264 content. Real world examples and hands-on projects with sample video files provide the expert training you need with tips and insights that everyone can benefit from. You'll learn: Basic methods, from preproduction through delivery, including capturing, processing, and compressing your video. Production essentials for sharing your footage on the Web, including setting up your Web page and server for seamless video playback and how to create your own video player. Advanced techniques, including building an index and play list, adding captions and banner ads, and designing a comprehensive video experiencefor your audience. The DVD-ROM includes complete sample Flash files as shown throughout the book. More than 2 GB of source files are provided, including High Definition (HD) clips, which you can use to perfect your video compression skills. The source files for each chapter are found in the corresponding Lessons folder on the disc. Robert Reinhardt is a highly respected authority on Flash and Flash video. He has authored or co-authored numerous books on Flash, including the Flash Bible and the Flash ActionScript Bible, and his blog and other online articles draw a wide audience. He has developed multimedia courses for educational facilities in Canada and the United States and is an Adobe Certified Instructor for Flash courses at Portland State University. He is a former Vice President of the Multimedia Platforms Group at Schematic and now works with a wide range of clients from his base in Portland, Oregon. A frequent presenter at conferences such as Flashforward, FITC, Flashbelt, and NAB, he is also a contributor at DesignProVideo.com. Forums and updates for this book can be found at FlashSupport.com, where you can share questions and answers with Robert and other readers.
Includes index. - Print version record
Keywords: Flash (Computer file); Flex (Computer file)